2016
DOI: 10.1017/s0954579416000687
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of internalizing and externalizing comorbidity across the early school years

Abstract: High rates of comorbidity are observed between internalizing and externalizing problems, yet the developmental dynamics of comorbid symptom presentations are not yet well understood. This study explored the developmental course of latent profiles of internalizing and externalizing symptoms across kindergarten, 1st, and 2nd grade. The sample consisted of 336 children from an urban, low-income community, selected based on relatively high (61%) or low (39%) aggressive/oppositional behavior problems at school entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
164
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(189 citation statements)
references
References 93 publications
(150 reference statements)
18
164
1
6
Order By: Relevance
“…For example, person-centered studies have identified unique classes that describe patterns of co-occurring symptomatology both cross-sectionally (Vaidyanathan, Patrick, & Iacono, 2011) and longitudinally through childhood (Patalay, Moulton, Goodman, & Ploubidis, 2017). Recent research investigating transitions between these cross-sectional classes over time indicate that transitions between 'pure' psychopathological classes (e.g., predominantly internalizing or externalizing) and comorbid classes are relatively common, with transitions more often observed to and from comorbid and predominantly externalizing classes (Basten et al, 2016;Kim & Eaton, 2017;McElroy, Shevlin, & Murphy, 2017;Willner, Gatzke-Kopp, & Bray, 2016). The findings of the present variable-centered study mirror these results; externalizing and p demonstrated stronger reciprocal relationships over time than internalizing and p. Indeed, it appears that those who score high on p initially could potentially develop more specific psychopathology in any of the three specific domains.…”
Section: Discussionmentioning
confidence: 99%
“…For example, person-centered studies have identified unique classes that describe patterns of co-occurring symptomatology both cross-sectionally (Vaidyanathan, Patrick, & Iacono, 2011) and longitudinally through childhood (Patalay, Moulton, Goodman, & Ploubidis, 2017). Recent research investigating transitions between these cross-sectional classes over time indicate that transitions between 'pure' psychopathological classes (e.g., predominantly internalizing or externalizing) and comorbid classes are relatively common, with transitions more often observed to and from comorbid and predominantly externalizing classes (Basten et al, 2016;Kim & Eaton, 2017;McElroy, Shevlin, & Murphy, 2017;Willner, Gatzke-Kopp, & Bray, 2016). The findings of the present variable-centered study mirror these results; externalizing and p demonstrated stronger reciprocal relationships over time than internalizing and p. Indeed, it appears that those who score high on p initially could potentially develop more specific psychopathology in any of the three specific domains.…”
Section: Discussionmentioning
confidence: 99%
“…3 externalising, or comorbid groupings at cross-sections in development, 14,15 and some studies have estimated the probabilities of transitioning between these groups over time. 16,17 This body of research suggests that to a greater extent, behavioural symptoms precede emotional symptoms, 11,12 a probably unsurprising finding given the former is more prevalent in childhood and the latter in adolescence. 18 Although there has been much focus on understanding longitudinal "which-comes-first" relationships between these domains, there have been no identified studies jointly identifying heterogeneous typologies of symptom development across both these domains longitudinally.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many factors may contribute to this inconsistency [15,16]. First, the high and stable comorbidity between EXT and INT in youth [25,26] may confound the association of each with alcohol use when the other one is not well adjusted for in the model [27]. Second, differing forms of internalising problems (global indices, depression, anxiety) may represent a different pathway to alcohol use [16].…”
Section: Introductionmentioning
confidence: 99%